PRINCIPLES OF STATE ORGANIZATION IN SURAH AN-NISA' (4): 58-59. - Ruhdiara, Ruhdiara (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2023)
Islamic State shows that the context of the discussion on the theme of government, requires to talk about the State, power, and politics and all things related to it. Because these three themes are integral (covering) in a government political system. Government and power are very urgent in a nation's community, because in this way the guarantee of an orderly life order, act based on the law, mutual trust among citizens, and the ideals of building justice for all citizens will be realized. Then the government too, as an unavoidable fact in the life of every citizen which has many meanings for them, individually and collectively. Government is the hope and opportunity to realize a prosperous and sovereign life by regulating the freedom and equal rights of its citizens. The method used in this journal article is a descriptive qualitative research method. The type of research used in the study is classified as library research, namely research in which data is processed and extracted from various books, newspapers, magazines and several writings that are related to this research and uses a normative legal approach. The results of this study indicate that in the implementation of the administration of the State, especially the government of the State in Surah An-Nisa {4}: 58-59 suggests that there are six principles of the use of political power or government power which can be seen as the principles of the administration of the State in the government system,